“The new face of the pandemic?” Parenthood in the face of a global crisis situation. Study on a Polish sample - Wioletta Tuszyńska-Bogucka; Roman Ryszard Szałachowski (Journal of Modern Science, 2025)
Objectives The purpose of this study is to examine the relationships between personal, family and environmental resources and the type of influence that the COVID-19 pandemic has had on parenting. We have used the term post-traumatic growth to describe the experience of positive changes that arise as a result of struggling with life crises.